The effect of two levels of dietary ractopamine hydrochloride (Paylean®) supplementation on growth performance, feed efficiency and quantitative carcass traits in finisher gilts - Webb, E.C. (Edward Cottington) (University of Pretoria, 2017)
Dissertation (MSc (Agric))--University of Pretoria, 2016.